Pelatihan dan Pendampingan Implementasi Aplikasi Wordwall dalam Pembelajaran Matematika Bagi Guru Kelas Rendah Sekolah Dasar Inpres Maulafa Kota Kupang - Juliana M. H. Nenohai; Siprianus S. Garak; Christine K. Ekowati; Patrisius Afrisno Udil (Jurnal Nasional Pengabdian Masyarakat, 2021)
The Covid-19 pandemic has changed face-to-face (offline) learning into online learning. This requires teachers to be able to adapt to utilizing technology-based learning media. Meanwhile, at the same time, teachers are not used to and have not been able to use various technology-based media in learning. One of the media that could be used is the wordwall application. This application is considered suitable because the appearance and operation are quite simple. In addition, this application can also be used as a learning media, a learning resource, and an assessment instrument. Therefore, training activities and mentoring in the implementation of wordwall applications in learning mathematics is one of the important and urgent needs for teachers today, especially in SD Inpres Maulafa, East Nusa Tenggara. This activity is carried out in training and mentoring through the material presentation, discussion, demonstrations and simulations, working in the group, and assistance. This activity showed that the participants were enthusiastic, active, and participative in participating in the training and mentoring. In addition, this activity can help participants overcome problems in designing thematic lessons. This activity can also increase teachers' knowledge about the application of technology to create learning media in the form of innovative elementary mathematics online learning media, namely through technical training in making learning media with wordwall applications in mathematics learning for teachers. Furthermore, this activity has also been able to increase the insight and ability of teachers to implement media in learning activities, namely through assistance in making learning designs using wordwall applications and assistance in implementing (strategy) learning using wordwall media